ROLE OF PLACENTAL DYSFUNCTION IN THE DEVELOPMENT OF PRE-ECLAMPSIA - Tishabayeva N.A (Scholar Express Journals, 2024)
Placenta-associated complication of pregnancy (fetal growth retardation, preeclampsia/eclampsia) are major causes of maternal and perinatal morbidity and mortality. A comparative assessment of the out –comes of pregnancy and childbirth in women with preeclampsia, diagnosed on the basis of various criteria for preeclampsia. A retrospective cohort study of pregnancy and childbirth outcomes was performed in 124 women with preeclampsia. The patients were divided into 3 groups depending on the preeclampsia criteria: in group 1 (58 women) there were women with preeclampsia, where hypertension + proteinuria was noted, in group 2 there were women (34 women) with preeclampsia, where there was hypertension + organ dysfunction, group 3 included women diagnosed with hypertension + uteroplacental dysfunction (32 women).
Keywords: preeclampsia; fetal growth retardation syndrome; placental dysfunction; pretern birth